Meeting the needs? Perceived support of a nurse‐led lifestyle programme for young adults with mental illness in a primary health‐care setting. (4th April 2017) - Rönngren, Ylva; Björk, Annette; Kristiansen, Lisbeth; Haage, David; Enmarker, Ingela; Audulv, Åsa
Abstract: Being a young adult with mental illness challenges all aspects of health, including an increased risk for developing lifestyle‐related diseases. There is a lack of lifestyle programmes in primary health care that target physical, mental, and social needs for young adults with mental illness. The aim of the present study was to describe the experiences of young adults with mental illness receiving support from a nurse‐led lifestyle programme, and how this support was related to their life context, including challenges and coping strategies. Two focus groups and six individual interviews were performed with 13 young adults (16–25 years), and analysed using a qualitative content analysis. The findings showed that the young adults experienced challenges in their daily lives, including psychiatric symptoms, lack of social understanding, and loneliness. The study indicated that the programme could support lifestyle habits with its components of supportive interpersonal relationships, awareness of coping strategies, understanding of health and illness, and cognitive support (e.g. schedules and reminders). However, the programme could not meet everyone's needs for new social relationships or more comprehensive support. Even so, this nurse‐led programme provides health information‐management strategies that could easily be integrated in a primary health‐care setting.